PRODUCTS OF WESTERN FORE-ELBRUS AUTONOMOUS ERUPTIONS: TRACES OF IMPACT GENESIS - Demina, L.; Promyslova, M.; Myshenkova, M.; Koronovsky, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Impactites are deep conversions of rocks under the effect of shock waves. Abbysal impact genesis is caused by deep explosions of condensed fluids. Fluidolites are characterized by specific structures and textures, mineral and chemical composition, and geological structure of bodies, which distinguishes them from similar sedimentary and tuffy rocks. The products of autonomous eruption foci in Western Elbrus reveal 6 different volcanic glasses, including those close to plagioclase and quartz. Such melts are products of endogenic impact genesis. In studying hypersthene, biotite, plagioclase of volcanites, there can be noticed a fundamental difference in their origin. Various genetic features of impactites are related to magmatism, deformation, and metamorphism. We propose an evolutionary model of the Neogene-Quaternary magmatism in the Caucasian sector of the Alpine orogen, with deep oxidation of transmagmatic fluids and endogenic impact-genesis being predominant. Oxidation of the main fluid components (H2, CH4, CO) occurs against significantly high heat flow and explosivity. Fluids concentration and their migration paths are closely linked to weakened areas of faulting in the crust. Crushing the substrate accelerates melting and promotes formation of chemically homogeneous magma. This is observed in the products of Bitiuk-Tube eruptions in the zone transitional from fluidolites to fluidolite-lavas and pumices. Abbysal explosions of fluids initiate both melting of the substrate and development of the channels through which magma intrudes. The first portions of eruptions are liquid-gas-solid slurry, extrinsic to form magma rocks, for magmatic material proper makes a small percentage. Subsequently, as the substrate melts down the share of gas-solid component in the eruption products decreases (as does magma flow velocity), while the share of melt and magma viscosity increase. Finally, the eruption is completed with magma melts, too sluggish to flow but viscous enough to form pumice. Endogenic impact genesis is likely to have occurred much wider than it is commonly believed. It both preceded ultrabasic and alkaline magmatism and played a leading role in the origin of acid magmas within collision areas in Earth's crust.
Keywords: fluidolites; deep fluids explosions; volcanism; impact genesis; Fore-Elbrus